PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN ATLET LARI 1500 METER ATLET ATLETIK PROVINSI RIAU - Indra Bakti Panjaitan; Slamet Slamet; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstark: The problem in this research is that athletes who don't perform well in running techniques tend to tire quickly. The title studied in this research y was